Comprehensive Diagnosis of Viral Hepatitis in Spain: Bases for Implementation - Joaquin Cabezas; Antonio Aguilera; Federico García; Raquel Domínguez-Hernández; Araceli Casado-Gómez; Nataly Espinoza-Cámac; Miguel Ángel Casado; Javier Crespo (Viruses)
In 2022, scientific societies agreed on a document with recommendations for a comprehensive diagnosis of viral hepatitis (B, C, and D). The aim was to evaluate the situation in Spain regarding the comprehensive diagnosis of viral hepatitis in a single blood draw before it is recommended. A panel of experts prepared a structured survey directed at hospitals (public or private with teaching accreditation) with ≥200 beds (sent 20 October 2022, closed 1 December 2022). The response rate was 61% (79/129; 52 hospitals with >500 beds). Among the participating hospitals, all could perform tests for HBsAg, anti-HCV, and HIV serology; 94% could perform PCR testing for HCV, 63% could test for anti-HDV, and 28% could test for HDV-RNA (67% [53/79] outsourced this testing). Point-of-care (POC) testing availability was low (24%), with 84% of these tests being supervised by the reference microbiological laboratory and the results being registered in the patients’ medical history. Ninety percent of the centers carried out the diagnosis in a single step (99% HCV, 70% HBV, 48% HDV, and 44% HBV-HDV). In addition, 77% used some communication strategy when an active infection was encountered (100% HCV, 49% HBV, and 31% HDV). Only 20% had an automated system for scheduling a specialist physician appointment. Most hospitals had the means for a comprehensive diagnosis of viral hepatitis in a single sample, but <50% could test for HBV/HDV. Alerts for continuity of care were available for HCV, but not HBV or HDV. POC device implementation is important for decentralized testing.